Vyhodnocení dodavatelského rizika prostřednictvím fuzzy logiky - Peterek, Daniel (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2020)
Předložená diplomová práce se zabývá vyhodnocením dodavatelů pro společnost Ferrit za využití fuzzy logiky. Hlavní část diplomové práce se zabývá tvorbou návrhů na řešení hodnocení dodavatelů vybrané společnosti. Rozhodovací modely jsou tvořeny v programech Microsoft Excel a MATLAB. Porovnání výsledků obou navržených rozhodovacích modelů je obsahem poslední části práce.

The presented diploma thesis deals with the evaluation of suppliers for the company Ferrit using fuzzy logic. The main part of the diploma thesis deals with the creation of proposals for the solution of the evaluation of suppliers of a selected company. Decision models are created in Microsoft Excel and MATLAB. The comparison of the results of both proposed models is the content of the part of the work.
Supplier Risk Assessment Using Fuzzy Logic
Keywords: Umělá inteligence; rozhodovací model; fuzzy logika; MATLAB; Microsoft Excel; Artificial intelligence; decision-making model; fuzzy logic; MATLAB; Microsoft Excel